The gender impact in earnings inequality: Evidence from Sri Lanka - Thankom Arun; Vani K. Borooah (International Journal of Economic Sciences and Applied Research, 2011)
This paper estimates an earnings function for Sri Lanka, followed by a decomposition analysis of male-female earnings suggest that the gender disparity in earnings largely represents discrimination against women. The findings showed that irrespective of their inferior labour market attributes, men had average earnings that were considerably higher than the female average and that this could be attributed entirely to discrimination in favour of male earners.
Keywords: O53; R2; O29; 330; inequality; earnings; gender; Sri Lanka